Central bank information and private-sector expectations - Jochen Güntner (Johannes Kepler University of Linz, Department of Economics, 2020)
Jarocinski and Karadi (2020) disentangle a pure information from the interest rate component of monetary policy surprises. This note quantifies the information revealed in FOMC announcements using forecast revisions from Blue Chip Economic Indicators. In response to a positive central bank information shock, survey participants revise their now- and short-term forecasts of real GDP growth upwards, while the corresponding revisions in the growth rate of the GDP de ator are mostly statistically insignificant.
Keywords: E32; E52; E66; 330; Blue Chip Economic Indicators; Central bank information shocks; Forecast revisions